2021
DOI: 10.1186/s12967-020-02674-5
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid-derived multipotent stromal cells drive diabetic wound healing through modulation of macrophages

Abstract: Background Cutaneous wounds in patients with diabetes exhibit impaired healing due to physiological impediments and conventional care options are severely limited. Multipotent stromal cells (MSCs) have been touted as a powerful new therapy for diabetic tissue repair owing to their trophic activity and low immunogenicity. However, variations in sources and access are limiting factors for broader adaptation and study of MSC-based therapies. Amniotic fluid presents a relatively unexplored source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…From Days 0 to 7, no difference was recorded in the residual wounds among the groups; however, the exudate in the control (gauze) group had increased significantly. Previous studies also showed that the time of chronic wound healing in db/db mice was significantly longer than that of normal wounds 46 . Until Day 10, new granulation tissues (GTs) and epithelialization degrees were significantly increased in CBS‐MSCs when compared with those in the other groups.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…From Days 0 to 7, no difference was recorded in the residual wounds among the groups; however, the exudate in the control (gauze) group had increased significantly. Previous studies also showed that the time of chronic wound healing in db/db mice was significantly longer than that of normal wounds 46 . Until Day 10, new granulation tissues (GTs) and epithelialization degrees were significantly increased in CBS‐MSCs when compared with those in the other groups.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies also showed that the time of chronic wound healing in db/db mice was significantly longer than that of normal wounds. 46 Until Day 10, new granulation tissues (GTs) and epithelialization degrees were significantly increased in CBS‐MSCs when compared with those in the other groups. The residual wound area (43.26 ± 4.60%) on Day 10 in CBS‐MSCs was significantly lower than that in the control (100.10 ± 0.05%, p < 0.05) (Figure 6c ).…”
Section: Resultsmentioning
confidence: 99%
“…AFSCs can differentiate along adipogenic, osteogenic, myogenic, endothelial, neurogenic, and hepatic pathways [ 126 ]. Moreover, Mu and co-workers [ 129 ] fully differentiated AFSCs into IPCs though a multi-step protocol. The differentiated cells expressed insulin, Glut2, Nkx6.1, and glucokinase.…”
Section: Perinatal Cellsmentioning
confidence: 99%
“…Administration of human AFSCs in a diabetic mouse model brought a reduction in the time of wound healing and a reduction of local inflammation, because of the increased secretion of IL-6, which is responsible for polarizing of macrophages in a pro-repair status [ 129 ]. Likewise, Sato, Y. et al [ 130 ] reported the ability of AFSCs to switch macrophages M1 to M2 in an animal model of perinatal sepsis, reducing inflammation.…”
Section: Perinatal Cellsmentioning
confidence: 99%
“…Various approaches have been developed to treat impaired diabetic wounds, such as the administration of cytokines and growth factors, [ 12–14 ] cell‐based therapies, [ 15,16 ] or negative pressure wound therapy (NPWT). [ 17 ] In recent years, many studies have focused on the development of biomimetic scaffold systems that are associated with peptide‐, cytokine‐, or growth factor‐based therapeutics.…”
Section: Introductionmentioning
confidence: 99%